Transverse Colonic Volvulus in a Child: Successful Management with Decompression and Delayed Laparoscopic Colopexy - Smith, Caroline; Cho, Alexander; Tsang, Thomas (European Journal of Pediatric Surgery Reports, 2013)
We report a case of colonic volvulus in a 7-year-old child with normal development. Operative findings at laparotomy showed a 270-degree transverse colonic volvulus (TCV), with colonic ligamentous attachment abnormalities. A loop ileostomy was formed following detorsion, with delayed laparoscopic colopexy. This is the first case to describe decompression by diversion ileostomy as acute management of TCV with delayed laparoscopic colopexy, so avoiding unnecessary bowel resection.
Keywords: large bowel volvulus; minimal access surgery; transverse colon